Fragmented Identities: The Impact of Ethnic Divides on Afghanistan’s Political Instability - Tayyab Ishtiaq; Arslan Asghar; Saqib Raza; Naseer khan Achakzai (Journal of Management Practices, Humanities and Social Sciences, 2024)
This article is the examination of the relationship held between the disjointed identities of Afghanistan and its stability in politics. This dynamic would assist to regularize the complexities how ethic differences between the two fueled terrorism and violence, and how the outsiders took advantages to enhance these divisions to motivate their agendas. The study employs a technique that entails multiple secondary data sources. Its analyses the indicator of political stability, the record of past and a thorough comprehension of different subtleties, however, inconsistency in Afghanistan politics is the main concern of this study. For country’s national unity, both factors, the richness of culture and cultural diversity are challenges as well as strength. The richness in culture proves as a fabric for national unity though it challenges for political stability and cohesion. As per the conclusion of the article, the stability of Afghanistan held by on the approaches and thought the government has for the ethic groups. Having good term with ethnic groups and to promote national unity, government can mitigate the conflict responsible for the stability of the nation. For addressing social inequalities and historical injustices, government can contribute of ethnic groups for its national unity. However, the external factor can play a significant role by supporting and encouraging inclusive thought and practices in Afghanistan, though it is also the duty of the international community to participate in Afghanistan's political stability. Ultimately, this article is a contribution to Afghanistan's journey towards stability, respecting the balance in identities and shared purposes.